Epidemiologic changes of infectious diseases in the post-SARS era in China, 2004-2018 - Yizhe Luo; Binxiong Wu; Yameng Xu; Lele Ai; Heng Lv; Jiahong Wu; Weilong Tan (BMC, 2023)
Abstract Objectives To outline 44 major infectious diseases in the post-SARS (severe acute respiratory syndrome) in China and describe their long-term trends and changes by age, sex, epidemic season, and province. Background After the outbreak of severe acute respiratory syndrome (SARS) in 2003, with the change of infectious disease prevention and control system and the improvement of residents' quality of life, the incidence and mortality of infectious diseases have undergone major changes. Methods The data of 44 major infectious diseases in China from 2004 to 2018 were obtained from the monthly analysis report of the China Information System for Disease Control and Prevention (CISDCP) and the Public Health Science Data Center. Joinpoint r regression models were used to examine trends in incidence and mortality for 44 major and important infectious diseases from 2004 to 2018. Results From 2004 to 2018, 20,105, 500, 772 patients (10, 306, 546, 523 males and 9, 798, 954, 249 females) were diagnosed with 44 major infectious diseases. The overall incidence of 44 infectious diseases increased significantly from 294.6 per 100,000 people in 2004 to 479.1 per 100,000 people in 2010, with 7.9% APC (95% CI 5.2% -10.7%, P < 0.001), then slowed, and then increased to 561.2 per 100,000 people in 2018, with 1.5% APC (-0.1%-3.2%, P = 0.070). The overall mortality rose significantly, from 0.49 to 1.13 per 100,000 people between 2004 and 2011, with an APC increase of 11.6% (7.7% -15.6%, P < 0.001), and then remained stable until 2018. Among these, the prevalence of vaccine-preventable diseases and gastrointestinal & enteroviral diseases remained high and increased year by year. Patients with zoonotic diseases have the greatest risk of death, while patients with sexually transmitted and blood-borne diseases have the greatest number of deaths. Incidence rates vary considerably across geographic regions. Western China has a disproportionate burden of infectious diseases compared with eastern regions. Conclusions After the event of SARS in 2003, infectious disease preventing and controlling model has undergone major changes in China, and certain achievements have been made in this field. Although overall morbidity and case fatality rates are still rising, they have leveled off. In reducing the disproportionate disease burden in the western region, expanding vaccination programs, preventing further increases in rates of sexually transmitted diseases, renewing efforts for emerging and persistent infectious diseases, and addressing seasonal and unpredictable outbreaks (such as the COVID-19 pandemic), there are still remain many challenges.